The role of civil society organizations in disaster response and relief: a case of Tokwe-Mukosi. - Zhou, Doreen (Midlands State University, 2017)
The research set out to assess the roles of civil society organizations in disaster response and relief in regards with the Tokwe-Mukosi flood disasters. The research used both primary and secondary sources to collect data. Qualitative data collection methods were applied through the use of interviews and questionnaires. The key findings of the study is that civil society organizations failed to provide adequate response and relief services to the victims of Tokwe-Mukosi flood disasters. Gaps identified in the response stage include poor dessermination of early warning messages as well as poor relocation of victims from the transit camps to Chingwizi holding camp. In the relief stage the research indentified failures in, the provision of clean water, health services, food and nutrition, also the education services were very poor. The research established that the civil society organizations had challenges in sourcing resources from the donor community and hence the inadequate response and relief at Chingwizi. The researcher recommends that, future response and relief services should be supported by vibrant preparedness plans such as timely and targeted early warning messages,strong financial resource base and coordination amongst stakeholders in disaster response and relief.